Verification of the eighth edition of the UICC‐TNM classification on surgically resected lung adenocarcinoma: Comparison with previous classification in a local center. Issue 1 (24th June 2021) - Minato, Hiroshi; Katayanagi, Kazuyoshi; Kurumaya, Hiroshi; Tanaka, Nobuhiro; Fujimori, Hideki; Tsunezuka, Yoshio; Kobayashi, Takeshi
Abstract: Background: The UICC 8th TNM classification of lung cancer has been changed dramatically, especially in measuring methods of T‐desriptors. Different from squamous‐ or small‐cell carcinomas, in which the solid‐ and the invasive‐diameter mostly agree with each other, the diameter of the radiological solid part and that of pathological invasive part in adenocarcinomas often does not match. Aim: We aimed to determine radiological and pathological tumor diameters of pulmonary adenocarcinomas with clinicopathological factors and evaluate the validity of the 8th edition in comparison with the 7th edition. Methods and Results: We retrospectively analyzed clinicopathological factors of 429 patients with surgically resected pulmonary adenocarcinomas. The maximum tumor and their solid‐part diameters were measured using thin‐sectioned computed tomography and compared with pathological tumor and invasive diameters. Overall survival (OS) rate was determined using the Kaplan–Meier method for different subgroups of clinicopathological factors. Akaike's information criteria (AIC) was used as a discriminative measure for the univariate Cox model for the 7th and 8th editions. Multivariate Cox regression analysis was performed to explore independent prognostic factors. Correlation coefficients between radiological and pathological diameters in the 7th and 8th editions were 0.911 and 0.888, respectively, without a significant difference. The major reasons for the difference in the 8th edition were the presence of intratumoral fibrosis and papillary growth pattern. The weighted kappa coefficients in the 8th edition were superior those in the 7th edition for both the T and Stage classifications. In the univariate Cox model, AIC levels were the lowest in the 8th edition. Multivariate analysis revealed that age, lymphovascular invasion, pT(8th), and stage were the most important determinants for OS. Conclusion: The UICC 8th edition is a more discriminative classification than the 7th edition. For subsolid nodules, continuous efforts are necessary to increase the universality of the measurement of solid and invasive diameters.